Mycetoma Epidemiology and Clinical Findings in Mogadishu, Somalia - Ahmet Doğan; Fadumo Nur Adan; Tigad Abdisad Ali; Ali Kutta Çelik; Ahmed Mohamed Ali (Journal of Tropical Medicine)
Conclusion: The frequency of myçetoma cases, which can involve all parts of the lower extremities, was determined, especially in Somali farmers. Difficulties in diagnosis and follow-up were analyzed.